PPAR-γ Gene Expression In Differentiated Adipocytes Derived From Mesenchymal Stem Cells Of Human Bone Marrow - Shadi Esmaeili; Saeid Kaviani; Mehrdad Norouzinia; Amir Atashi; Masoud Soleimani; Saeid Abroun; Rasoul Razavi Babaheidari; Zahra Zonoubi; Fakhreddin Saba (Tehran University of Medical Sciences, 2015)
Background and Aim: Obesity is now considered as one of the main risk factors of certain known diseases such as cardio-vascular diseases, non- insulin-dependent diabetes, and common cancers. Moreover, the increase of white fat tissue is known as a main factor in the obesity process, in terms of physiology and pathology. Therefore, the understanding of adipocytes differentiation processes is crucial. Materials and Methods: In this study, mesenchymal stem cells (MSCs) were isolated from human bone marrow by ficol-gradient, and then, their surface markers were confirmed by flow cytometry. Osteoblastic and adipocytes differentiation were done by dexamethasone protocol and confirmed by staining. Then qualitative and quantitative expressions of PPARgamma (PPAR-γ) gene as an important transcription factor in the differentiation of fat were studied by RT-PCR and REAL TIME PCR before and after differentiation into adipocytes. For statistical analysis, paired t-test was performed, using pfaffl and graph pad software. Results: PPAR-gamma gene expression showed a significant increase after differentiation of human bone marrow mesenchymal stem cells into adipocytes (p<0/05). Conclusion: According to the results, the PPAR-γ gene acts as one of the important factors in the differentiation of MSCs into adipocytes. In brief, the inhibition of this gene's expression to prevent obesity is suggested as an idea for treatment in the future.